The cow and the butterfly - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The spectre of rinderpest has long haunted Africa, ever since its arrival on the continent through the Ethiopian port of Massawa in 1888. Since then it has spelt death to millions of animals. It seems to have largely disappeared, at least for the...